Edukasi Gizi dengan CAMIL Sama Efektif dengan Leaflet dalam Prilaku Pencegahan Anemia pada Ibu Hamil - Rista Elmika; Demsa Simbolon; Emy Yuliantini (Poltekkes Kemenkes Jakarta III, 2018)
Iron nutritional anemia is anemia caused by iron deficiency in the blood, meaning the concentration of hemoglobin in the blood is less than 11 gr / dl. According to WHO, the incidence of pregnancy anemia ranges between 20% and 89% by setting Hb 11 g% (g / dl). The pregnancy anemia rate occurred 3.8% in the first trimester, 13.6% trimester II, and 24.8% in the third trimester. To know the effectiveness of CAMIL media (iron anemia disc pregnant mother) to behavior of prevention of iron anemia in pregnant mother in work area of ​​Beringin Raya Public Health Center of Bengkulu City. This type of research uses Quasy Experimental Study with Pretest-Postest Control Group Design. The population in this study were pregnant women listed in the Register of Beringin Raya Public Health Center of Bengkulu Year 2018. total samples were 40 respondents.20 respondents of the intervention group and 20 control groups. Data analysis using T-test. The result of the research is the effect of CAMIL on knowledge, attitude and action where the sign value 0.000 <0.05. While the Leaflet of behavior (knowledge, attitude, and action) there is influence where the sign value is 0.000 <0.05. There is no difference of knowledge on CAMIL group and leaflet where sign value is 0.106> 0.05. For attitudes on the CAMIL group and the leaflet is the same where the sign value is 0.146> 0.05. Action on the CAMIL group and the same leaflet where the sign value is 0.064> 0.05. Conclusion From the results of this study it can be concluded that health education is important to improve knowledge, attitude, and action, using CAMIL media and leaflets, both media are equally efketif because it is written with the added pictures